Comparative analysis of methods for the microcircuit assembly on flexible polyimide carriers - Verbitskiy, V. G.; Zhora, V. D.; Grunyanskaya, V. P.; Plis, N. I. (Technology and design in electronic equipment, 2013)
The article presents a classification of methods for the microcircuit assembly with the use of flexible polyimide carriers of different types, and their comparative analysis. The most appropriate method for the manufacturing of flexible dual-layer carriers is singled out.